Theorizing masculinities - Brod, Harry, 1951-; Kaufman, Michael, 1951-; Sage eBooks; Men's Studies Association (U.S.) (Thousand Oaks, Calif. ; London : SAGE, 1994)
Contributors from diverse backgrounds address the different disciplinary roots of theories of masculinity - sociology, psychoanalysis, ethnography, and inequality studies. Chapters theoretically model many issues central to the study of men - power, ethnicity, feminism, homophobia - or develop theoretical explanations of some of the institutions most closely identified with men including the military and the men's movement.
"Published in cooperation with the Men's Studies Association, a task group of the National Organization for Men Against Sexism."
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Men's studies -- Philosophy; Masculinity; Men -- Psychology; Men -- Attitudes; Sexual orientation; Feminist theory; Electronic books